History and war as a cause of construction movement in the view of Will Durant and Machiavelli - Assis. Lect. Farhang Noori Mahmood; Assistant Lecturer: Saman Othman Ali (Journal of College of Education, 2025)
History and war as a cause of the construction movement are inseparable twins. These two subjects have always been the deep intellectual point behind any change, because an important part of civilization's progress begins with the end of wars Construction In the view of many thinkers, conflict and breaking each other is a pre-civilization stage where one force can break the waist of another force and dominate the center of construction and become a turning point Motivate constructive movements, and examine past examples of historical events that have led to positive change, war as a cause of constructive movements and the emergence of history, study the role of war in stimulating constructive movements, analyze the impact of conflict on change and development.Will Durant's views on history and its influence on constructive movements and discuss key ideas and concepts in this regard are discussed, as well as Machiavelli's views on war and its role in shaping the development of societies It does history, war, and constructive movements, highlighting the perspectives of Will Durant and Machiavelli.
Keywords: Machiavelli; Will Durant; history; war; construction